Integrative pharmacology reveals the mechanisms of Erzhi Pill, a traditional Chinese formulation, against diabetic cardiomyopathy. (5th October 2022) - Peng, Mingming; Xia, Tianyi; Zhong, Yanmei; Zhao, Mantong; Yue, Yimin; Liang, Lanyuan; Zhong, Renxing; Zhang, Han; Li, Chuanqiu; Cao, Xia; Yang, Mengru; Wang, Yi; et al.
Abstract: Ethnopharmacological relevance: Erzhi Pill (EZP) is a traditional Chinese prescription that has marked effects in treating type 2 diabetes mellitus and diabetic nephropathy. However, its underlying pharmacological mechanisms in the treatment of diabetic cardiomyopathy (DCM), remain to be elucidated. Aim of the study: This study aimed to apply an integrative pharmacological strategy to systematically evaluate the pharmacological effects and molecular mechanisms of EZP, and provide a solid theoretical basis for the clinical application of EZP in the treatment of DCM. Materials and methods: In this study, the potential targets and key pathways of EZP were predicted and validated using network pharmacology and molecular docking, respectively. Changes in cardiac metabolites and major metabolic pathways in rat heart samples were examined using 1 H-nuclear magnetic resonance (NMR) metabolomics. Finally, biochemical analysis was conducted to detect the protein expression levels of key pathways. Results: We found that EZP decreased fasting blood glucose (FBG), triglycerides (TG), total cholesterol (TC), and low-density lipoprotein (LDL) levels, increased high-density lipoprotein (HDL) levels in the serum, and alleviated the morphological abnormalities of the heart tissue in diabetic rats. Furthermore, EZP effectively restored superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), caspase-3, caspase-8, and caspase-9 activity levels, as well as the levels of reactive oxygen species (ROS), malondialdehyde (MDA), B-cell lymphoma (Bcl)-2, and Bcl-2-associated X protein (Bax) in the heart tissue. Network pharmacology prediction results indicated that the mechanism of EZP in treating DCM was closely related to apoptosis, oxidative stress, and the HIF-1, PI3K-Akt, and FoxO signaling pathways. In addition, 1 H-NMR metabolomics confirmed that EZP primarily regulated both energy metabolism and amino acid metabolism, including the tricarboxylic acid (TCA) cycle, ketone bodies metabolism, glutamine and glutamate metabolism, glycine metabolism, and purine metabolism. Finally, immunohistochemistry results indicated that EZP reduced the expression levels of p-AMPK, p-PI3K, p-Akt, and p-FoxO3a proteins, in the heart tissue of DCM rats. Conclusion: The results confirmed that the overall therapeutic effect of EZP in the DCM rat model is exerted via inhibition of oxidative stress and apoptosis, alongside the regulation of energy metabolism and amino acid metabolism, as well as the AMPK and PI3K/Akt/FoxO3a signaling pathways. This study provides an experimental basis for the use of EZP in DCM treatment. Graphical abstract: Image 1